2013
DOI: 10.1175/jcli-d-12-00471.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Strong Tropical Volcanic Eruptions on ENSO Simulated in a Coupled GCM

Abstract: The impact of strong tropical volcanic eruptions (SVEs) on the El Niño–Southern Oscillation (ENSO) and its phase dependency is investigated using a coupled general circulation model (CGCM). This paper investigates the response of ENSO to an idealized SVE forcing, producing a peak perturbation of global-mean surface shortwave radiation larger than −6.5 W m−2. Radiative forcing due to volcanic aerosols injected into the stratosphere induces tropical surface cooling around the volcanic forcing peak. Identical-twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
140
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(165 citation statements)
references
References 50 publications
24
140
1
Order By: Relevance
“…This warming event after volcanic eruptions has been reflected in many proxy data (Fig. 1) and previous simulations (Ohba et al 2013;Maher et al 2015;Stevenson et al 2016). However, the location of the maximum warming in the El Niño mature phase in Vol (Fig.…”
Section: Observed and Simulated Sst Changes In The Equatorial Pacificsupporting
confidence: 63%
See 2 more Smart Citations
“…This warming event after volcanic eruptions has been reflected in many proxy data (Fig. 1) and previous simulations (Ohba et al 2013;Maher et al 2015;Stevenson et al 2016). However, the location of the maximum warming in the El Niño mature phase in Vol (Fig.…”
Section: Observed and Simulated Sst Changes In The Equatorial Pacificsupporting
confidence: 63%
“…The process by which tropical volcanic eruptions influence ENSO has been studied via numerical simulation (Mann et al 2005;Emile-Geay et al 2008;Zanchettin et al 2012;Ohba et al 2013;Ning et al 2017;Predybaylo et al 2017;Stevenson et al 2017). Mann et al (2005) explained Sea Surface temperature (SST) change over the eastern Pacific after volcanic eruptions by utilizing an air-sea coupled model (Zebiak and Cane 1987), invoking the dynamical thermostat hypothesis (Clement et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling studies do not yield consistent results and show both an El Niño-like (3)(4)(5) or La Niña-like (6,7) anomalies following a tropical eruption. Recent studies have also suggested that volcanic eruptions can have a large imprint on ocean circulation, affecting the strength of the Atlantic Meridional Overturning Circulation (AMOC) (8-12) on 5-to 20-y timescales and inducing ocean heat content (OHC) anomalies (13,14) that may persist for decades.…”
mentioning
confidence: 91%
“…An important climatic response to eruptions is their effect on the El Niño/Southern Oscillation (6)(7)(8): Within the eruption year, previous work indicates that the tropical response appears La Niña-like (9,10), with enhanced El Niño likelihood the following year (6,11). However, debate remains regarding the significance of and mechanisms for these responses (7,8,12,13), as well as the degree to which they depend on the characteristics of the eruption [i.e., hemispheric loading (13)(14)(15), strength (8), or initial conditions (12)]. Understanding all of these factors is crucial for assessing the potential risks associated with future large eruptions.…”
mentioning
confidence: 99%